New Insights Into Implementation of Mesenchymal Stem Cells in Cancer Therapy: Prospects for Anti-angiogenesis Treatment - Javan, Mohammad Reza; Khosrojerdi, Arezou; Moazzeni, Seyed Mohammad (Frontiers in Oncology, 2019)
Tumor microenvironment interacts with tumor cells, establishing an atmosphere to contribute or suppress the tumor development. Among the cells which play a role in the tumor microenvironment, mesenchymal stem cells (MSCs) have been demonstrated to possess the ability to orchestrate the fate of tumor cell, drawing the attentions to the field. MSCs have been considered as cells with double-bladed effects, implicating either tumorigenic or anti-tumor activity. On the other side, the promising potential of MSCs in treating human cancer cells has been observed from the clinical studies. Among the beneficial characteristics of MSCs are the natural tumor-trophic migration ability, providing facility for drug delivery and, therefore, targeted treatment to detach tumor and metastatic cells. Moreover, these cells have been under engineering approaches, due to their easily implementing traits, in order to obtain desired properties of expressing anti-angiogenic, anti-proliferative, and pro-apoptotic, according to the tumor type. Tumor angiogenesis is the key characteristic of tumor progression and metastasis. Manipulation of angiogenesis has become an attractive approach for cancer therapy since introduction of first angiogenesis inhibitor, namely bevacizumab, for the therapy of metastatic colorectal cancer. This review tries to conclude the approaches, with focus on anti-angiogenesis approach, in implementing the MSCs to combat against tumor cells progression.